TRENDS IN THE USE OF NATURAL AGENTS FOR CHRONIC WOUND CARE IN DEVELOPING COUNTRIES: A SCOPING REVIEW - Putra Ardhana; Lydia Moji Lautan (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Background: Chronic wounds remain a major healthcare challenge in developing countries due to limited access to advanced wound care technologies and the high cost of treatment. These limitations have encouraged the use of natural agents as affordable alternatives for chronic wound management. Natural agents such as honey, Aloe vera, propolis, virgin coconut oil, Centella asiatica, and herbal extracts have demonstrated antimicrobial, anti-inflammatory, and tissue-regenerative properties. Purpose: This scoping review aimed to map trends in the clinical use of natural agents for chronic wound care in developing countries from 2010 to 2024, including the types of agents used, therapeutic outcomes, safety, cost-effectiveness, and emerging clinical applications. Methods: This review followed the Arksey and O'Malley methodological framework and the PRISMA-ScR guidelines. A systematic search of PubMed, ScienceDirect, Scopus, and Google Scholar identified studies published between January 2010 and October 2024. Eligible studies were screened, selected, and synthesized. Results: Of 2,876 records identified, 15 studies met the inclusion criteria. The findings showed a gradual evolution in the clinical use of natural agents. Honey and Aloe vera predominated in earlier studies, while more recent research explored propolis, virgin coconut oil, olive oil–honey combinations, Centella asiatica, and plant-based hydrogels. Most studies focused on diabetic foot ulcers. Overall, natural agents accelerated wound healing, enhanced granulation tissue formation, reduced wound size and infection, and provided cost-effective alternatives to conventional wound care. Conclusion: Natural agents have evolved from conventional single-agent therapies to diverse bioactive formulations integrated with modern wound care. Current evidence supports their effectiveness, affordability, and potential role in improving chronic wound management, particularly in developing countries and other resource-limited healthcare settings.